Enhancement of Himalayan irregular stone masonry buildings for resilient seismic design - Khadka, Shyam Sundar; Acharya, Sabin; Acharya, Ayush; Veletzos, Marc J. (Frontiers in Built Environment, 2023)
In the Himalayan region of Nepal, stone masonry has been used as the primary building material for structures with or without mud mortar for centuries. In three distinct remote rural villages, a thorough structural survey of about 223 buildings was carried out with an emphasis on their structural irregularities. The thickness of masonry walls frequently varies between floors, causing mass irregularities. Openings in the front wall of the building are not symmetrical in the vertical direction, causing in-plane discontinuity. There is also out-of-plane offset irregularity due to the cross wall in the ground floor only. These buildings are irregular in many aspects and were constructed without seismic consideration. This type of construction is more susceptible to earthquakes as a result of these irregularities. In this study, a thorough examination of a typical building is conducted using construction information obtained following the 2015 Gorkha earthquake. The database for each structural typology is prepared in this paper with an emphasis on construction practice to enhance seismic design. The use of mud/cement mortar is found to be extremely sparse, and the use of timber bands at various heights along the height of the masonry wall and an inappropriate connection between the wall and the roof are also both found to be negligible. The three main community-learned improvements following damages are the replacement of the gable wall with metal sheet, reduction of individual stone masonry homes to one story, and lighter construction on upper stories for hotel buildings. Based on regional building techniques, nonlinear finite models for typical and enhanced buildings were simulated. Due to irregular stone units, construction variability, and constrained linear behavior, stone masonry with and without mud mortar presents difficulties for detailed numerical analysis. The development of such structures using mud/cement mortar and other regional materials, with careful attention to detail, has been found to have significant potential as a seismically resilient building form.